ANALYSIS OF THE RESULTS OF THE QUESTIONNAIRE ON THE FACTORS OF INCREASING THE LEVEL OF PHYSICAL ACTIVITY OF SCHOOLCHILDREN (Physical Culture and Sport: Scientific Perspective, 2025)
The article presents an analysis of the results of a survey on the factors of increasing the level of physical activity of schoolchildren among teachers. The purpose of the scientific article is to identify the key factors that contribute to increasing the level of physical activity and patriotic education of schoolchildren, based on the analysis of the results of a survey of pedagogical staff. The survey was conducted to collect the results of a survey of pedagogical staff on the key areas of popularization of physical activity among schoolchildren in the context of modern challenges and threats. The results of the survey of pedagogical staff showed the importance of a comprehensive approach to increasing the level of physical activity among schoolchildren, including various methods to improve physical and patriotic education. The findings also emphasize the need to adapt educational programs to current challenges and threats, which will increase their effectiveness in the context of strengthening the state's defense capabilities. The most effective measures to increase physical activity and patriotic education are the organization of school sports sections, clubs and
Keywords: physical activity; schoolchildren; teachers; patriotic education and the state's defense capability